2016
DOI: 10.15587/1729-4061.2016.86435
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric research into fish and plant semifinished products made of raw and blanched tissues of Azov goby and wheat bran

Abstract: Проведено визначення термогравіметричних показників та диференційно-термічний аналіз нативних та відновлених рибо-рослинних напівфабрикатів на основі бичка азовського. Здійснено порівняльну характеристику кількості адсорбційно та капілярно зв'язаної вологи досліджуваних зразків. Вивчено вплив рослинної сировини, гігротермічної обробки та процесу дегідратації рибо-рослинних напівфабрикатів на форми та енергію зв'язку вологи Ключові слова: термогравіметричний аналіз, рибо-рослинні напівфабрикати, бичок азовський… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This weight loss is most probably caused by bound moisture evaporation. 6,7 Thus, it could be concluded that, despite all the stages of drying, the investigated MCC still contained 0.4% moisture.…”
Section: Thermogravimetric and Differential Thermal Analysesmentioning
confidence: 86%
See 1 more Smart Citation
“…This weight loss is most probably caused by bound moisture evaporation. 6,7 Thus, it could be concluded that, despite all the stages of drying, the investigated MCC still contained 0.4% moisture.…”
Section: Thermogravimetric and Differential Thermal Analysesmentioning
confidence: 86%
“…The measurements were made within the temperature range of Т = (20÷250) °C and with the heating rate of 5 °C/min. 6,7 The samples for the dielectric investigation were prepared by pressing MCC powder, under vacuum at 10 -2 mm Hg, at a pressure of 36 MPa, after previously drying this powder at 105 °С during 30 minutes for final removal of moisture. Samples with the diameter of 45 mm and thickness of 0.5 mm were made.…”
Section: Methodsmentioning
confidence: 99%
“…Signals from thermocouples, differential transformer and inductive coil are fed through an amplifier. Thus, we synchronously get curves of the simple (T) and differential thermal (DTA) analyzes, mass loss curve (TG) and mass loss speed curve GTG) on a computer monitor [10].…”
Section: Food Science and Technologymentioning
confidence: 99%